Ælfric's letter to the monks of Eynsham - Jones, Christopher A. (Christopher Andrew) (Cambridge studies in Anglo-Saxon England, 2004)
The Anglo-Saxon scholar Ælfric composed an important set of Latin liturgical instructions for his fellow monks. This book contains a new edition of the Latin text with a critical apparatus, and the only complete English translation, along with a commentary and substantial introductory chapters.